Marathon fighters and men of maple ancient Acharnai - Kellogg, Danielle L. ca. 20./21. Jh (Oxford Univ. Press, 2014)
Acharnai was the largest of the Kleisthenic demes. Kellogg provides an investigation into the workings of a rural deme. She combines literary, prosopographical, epigraphical, and archaeological evidence to create an encompassing overview of this dynamic and historical settlement with a well-developed identity and unique traditions